الثقافة التنظيمية وكفاءة الأداء وفق معاييرالجودة لأعضاء هيئة التدريس في كلية التربية الرياضية جامعة صلاح الدين– أربيل - عولا, سرتيب عمر; اسماعيل, عوزير سعدي (Sulaimani Journal for Humanities, 2018)
Organizational culture is a system of ideas, beliefs, customs, traditions, values, methods of thinking and action, patterns of behavior, expectations and standards that the members of the organization meet, influence their behavior in the university or colleges, shape their personalities and control their experiences and influence the production, And performance at work. Search Goal: Knowledge of the level of organizational culture prevailing teachers in the Faculty of Physical Education - University of Salahaddin - Erbil. Recognition of the level of performance evaluation of teachers at the Faculty of Physical Education - Salahuddin University. What are the relationships between the organizational culture and the evaluation of performance in the Faculty of Physical Education - University of Salahaddin - Erbil. - The research community: The research community was represented in a sample of all the members of the faculty who have a doctorate and master's degree in different specialties in the Faculty of Physical Education at the University of Salahaddin / Erbil. - For the purpose of achieving the goal of the research has been used the tools of organizational culture and the performance of Adari: For the purpose of measuring or identifying the level of organizational culture and its relation to the performance of the administrative staff of the Faculty of Physical Education at the University of Salahaddin was used to measure the (organizational culture), (performance of Aladdari) and therefore was presented to a group of experts and specialists in the field of management and sport and sports psychology, After the validity and reliability of the instruments, the two tests were applied to the sample of the study. After collecting and unloading the data, they were statistically processed by the appropriate statistical means, namely the arithmetic mean, the standard deviation, the percentage and the correlation coefficient. And reached the most important results: - The study showed different levels in the dimensions of the organizational culture and evaluation of the performance of the administrators from the point of view of faculty members College Physical Education - University Salahaddin / Erbil. - The results showed the existence of a positive relationship between the organizational culture and the performance evaluation of the administrators from the point of view of faculty members in the Faculty of Physical Education - University of Salahaddin / Erbil The researchers recommended: - The need to work to increase the awareness and knowledge of the macro-administrators of the prevailing organizational culture General, and highlight the organizational cultures that help to increase the performance of the administration, especially through the practice of fieldwork and theoretical. - Participate in the training courses and benefit from the expertise and creativity of distinguished administrators through the adoption of seminars, lectures, seminars and workshops by those responsible for training operations on the methods and elements of organizational culture to achieve and develop the performance of administrators.